Urban land use and management drive soil pollution across urban and nearby natural ecosystems in the Iberian Peninsula - Andrea C. Sala-Navarro; Nuria Casado-Coy; Axel Campos-Castro; Camelia Algora; Elena Aguilar-Santana; Kaiyan Zhai; Josu G. Alday; Cristina Armas; C. Guillermo Bueno; Leonor Calvo; María Dolores Carmona-Yáñez; Giada Centenaro; et al. (Journal of Hazardous Materials, 2026)

The rule 3-30-300 for a healthier and greener compact Mediterranean city - Felipe Torrentí; Pierre Sicard; Luís Alonso; Vicent Calatayud (Journal of Environmental Management, 2026)

Consistent topsoil carbon density and driving factors in urban greenspaces and natural ecosystems - Beatriz Jiménez-Prieto; Pablo García-Palacios; Carmen Lorenzo-Rodríguez; Elena Aguilar-Santana; Josu G. Alday; Camelia Algora; Cristian Carrillo-Guzmán; Cristina Armas; Felipe Bastida; Leonor Calvo; María D. Carmona-Yáñez; Axel Campos-Castro; et al. (Plant and Soil, 2026)
Background Urban greenspaces have the potential to mitigate urban carbon footprints by storing soil organic carbon (SOC). Different management and plant communities associated with different types of urban greenspaces may hold contrasting SOC, as well as different proportions of particulate (POC) and mineral-associated organic carbon (MAOC). In addition, management could outweigh the effects of climate or soil properties as drivers of urban SOC storage, in contrast with natural environments. Methods We analyzed SOC, POC and MAOC densities (kg m −2 ) in topsoil (0-10 cm) across 27 cities in the Iberian Peninsula with contrasting climatic and edaphic conditions. At each city, we compared four types of urban greenspaces (golf courses, roundabouts, urban farms, and parks) with a nearby natural ecosystem. Results Results revealed that, despite large differences in their typology, contrasting urban greenspaces stored comparable topsoil SOC and MAOC densities to natural ecosystems. Golf courses and urban farms also showed similar POC density to natural ecosystems, whereas parks and roundabouts had lower amounts of this carbon fraction. Consistent with global natural patterns, MAOC dominated over POC in the topsoil, and both carbon fractions showed an inverse correlation with mean annual temperature. While MAOC exhibited saturation at higher SOC levels, POC steadily increased. Conclusion Although urban greenspaces are usually neglected in global soil carbon assessments, our study shows that, compared to natural ecosystems (median: 2.42 kg m −2 ; interquartile range: 1.77), these areas store an equally important density of carbon in the topsoil (median: 2.26 kg m −2 ; interquartile range: 1.30), and this carbon exhibits similar fraction dominance, temperature influence, and saturation across large spatial gradients.

Historical biogeography of the diverse Neotropical seasonal killifishes of the Austrolebias Genus Group: potential environmental drivers of diversification - Sabrina Portelli; Wilson Sebastián Serra Alanís; Luis Esteban Krause Lanés; Martin Miguel Montes; Guillermo Enrique Terán; Matheus Vieira Volcan; Felipe Alonso (Zoologischer Anzeiger, 2026)

Dual molecular axis of resistance and immunoresponsiveness to BCG in pT1 non-muscle invasive bladder cancer: Insights from HER-2, SERBP1, HABP4, and IFN-γ profiling - João Carlos Cardoso Alonso; Juliana Mattoso Gonçalves; Gabriela Cardoso de Arruda Camargo; Gabriela de Oliveira; André da Silva Santos; Adriano Angelo Cintra; Fabio Guimaraes; Leandro Luiz Lopes de Freitas; Martim Corrêa Bottene; Jean Felipe Prodocimo Lestingi; Jörg Kobarg; Wagner José Fávaro (Tissue and Cell, 2026)

Early response of soil bacterial communities to soil burn severity in pine and shrub vegetation after wildfire in temperate-humid climate - Juan A. Rubiolo; Felipe García-Oliva; José A. Vega; Yunuen Tapia-Torres; José M. Fernández-Alonso; Paulino Martínez; M. Teresa Fontúrbel (Science of The Total Environment, 2025)

Floral resources in the surrounding landscape matrix augment plant species richness of bumblebee pollen loads in small, fragmented calcareous grasslands - Evan Taylor Sloan; Ira Hannappel; Annika L. Hass; Alexander Keller; Felipe Librán-Embid; Jelle Devalez; Elena Velado-Alonso; Triin Reitalu; Catrin Westphal; Hans Jacquemyn (Biological Conservation, 2025)

Evolved bet-hedging through maternal effects: developmental trajectory variation in annual killifish across a wet–dry cycle - Vinicius Weber; Felipe Alonso; Robson S. Godoy; Luis E. K. Lanés; Mateus M. Pires; Adriana Gava; Cristina Stenert; Leonardo Maltchik (Hydrobiologia, 2025)

The rise of a Titan: a new species of the giant Titanolebias killifishes, and its phylogeny (Cyprinodontiformes: Rivulidae) - Felipe Alonso; Guillermo Enrique Terán; Wilson Sebastián Serra Alanís; Marcos Martin Waldbillig; Martin Miguel Montes; Baltazar Bugeau; Jorge Adrian Barneche; Marina Ibañez Shimabukuro; Francisco González Táboas; Malena Maroli; Matías Jesús Almeida (Zoologischer Anzeiger, 2025)

Clinical and immunohistochemical effects of OncoTherad (MRB-CFI-1) nanoimmunotherapy on SERBP1, HABP4, CD44 and Ki-67 in BCG-unresponsive non-muscle invasive bladder cancer - Maria Izabel de Barros Frazão Salmazo; João Carlos Cardoso Alonso; Gabriela Cardoso de Arruda Camargo; Gabriela de Oliveira; André da Silva Santos; Monaliza Ávila; Isadora Manzato Roberto; Leandro Luiz Lopes de Freitas; Martim Corrêa Bottene; Jean Felipe Prodocimo Lestingi; Paulo Henrique Ferreira Caria; Nelson Durán; et al. (Tissue and Cell, 2025)

Analysis of the Ocean–Atmosphere Interface in the Brazil Current Region - Raquel Machado Machado; Douglas da Silva Lindemann; Luís Felipe Ferreira de Mendonça; Rose Ane Pereira de Freitas; Ítalo Seilhe Reis; Marcelo Felix Alonso (International Journal of Climatology, 2025)
The Brazil current (BC) is a westerly current that flows south along the Brazilian coast, being part of the Southern Brazilian Continental Shelf (SBCS). Recent studies have indicated a trend towards intensification and a shift to the south of the region where this current predominates. We analysed the seasonality of the relationship between atmospheric variables and sea surface temperature (SST) with potential trends and changes in the spatio‐temporal pattern of these variables from 1980 to 2020 over the BCs area in the South Atlantic Ocean. For this purpose, monthly data on SST, air temperature at 2 m above the surface (T2M), mean sea level pressure (MSLP), zonal wind (U10) and meridional wind (V10), obtained from ERA5 reanalysis, were used. Descriptive statistical analyses, trends using the Mann‐Kendall test, correlation matrices and Pettitt's test revealed a significant spatial correlation between the variables, with temporal trends of variation, especially over the BCs area. The meridional (zonal) wind predominantly exhibited a north–south (west–east) direction, supporting the hypothesis that the study region was displaced. Additionally, statistically significant positive trends were observed for SST (0.02°C ∙ dec −1 in austral autumn, winter and spring and 0.01°C ∙ dec −1 in austral summer), T2M (0.02°C ∙ dec −1 in austral winter and spring), MSLP (0.05°C ∙ dec −1 in austral autumn) and negative for U10 (−0.01°C ∙ dec −1 in austral spring). Pettitt's test results confirm significant changes in the behaviour of most analysed variables from the late 1990s to the early 2000s. The post‐breakpoint periods of the variables consistently showed above‐average values compared to the pre‐breakpoint periods, supporting positive upward trends consistent with literature findings. In particular, they highlight the notable upward slope in SST in the BC region.

Matisia boyacensis (Malvaceae): a new species from the premontane forests of the Cordillera Oriental of Colombia - Andrés Felipe Torrejano-Munevar; Carlos Andrés Paz López; José Luis Fernández-Alonso (Brittonia, 2025)

Net primary productivity but not its remote‐sensing proxies predict mammal diversity in Andean‐Amazonian rainforests - Kim L. Holzmann; Pedro Alonso‐Alonso; Yenny Correa‐Carmona; Andrea Pinos; Felipe Yon; Alejandro Lopera; Gunnar Brehm; Alexander Keller; Ingolf Steffan‐Dewenter; Marcell K. Peters (Ecology, 2025)
Tropical forests are disappearing, but we have a limited understanding of the factors driving species coexistence in mammal communities of old‐growth forest ecosystems. The total energy that is bound by plants is assumed to be a key factor determining mammalian species richness, but accurately measuring energy flows in complex ecosystems is difficult, and most studies therefore rely on remote‐sensing‐based surrogates of net primary productivity (NPP). We monitored mammal species richness across three seasons using camera traps on 26 study plots along a forested, elevational gradient from 245 to 3588 m above sea level in southeastern Peru for which a unique dataset on field‐measured NPP exists. Using linear‐regression models and path analysis, we disentangled the effects of climate and NPP on the diversity of mammals, testing the predictions of the more‐individuals hypothesis, stating that energy availability drives the number of individuals and, thus, the number of coexisting species. We compared detailed field measurements of NPP with remote‐sensing products (MODIS NPP and MODIS NDVI). Mammal species richness, abundance, and biomass decreased in a negative exponential pattern with elevation. Field‐measured data on NPP, which was largely driven by temperature, was a strong predictor of both abundance and species richness, while remotely sensed proxies for NPP failed to accurately predict mammal diversity. Our study underpins the importance of field‐based ecosystem data and emphasizes the role of high primary productivity for maintaining diverse mammal communities, which is a particularly pressing issue in light of recent anthropogenic impacts on the Amazonian forest system.

Integrative phylogeny of Corydoradinae (Siluriformes: Callichthyidae) with an emphasis on northwestern La Plata species, including descriptions of a new genus and species - Felipe Alonso; Guillermo Enrique Terán; Gastón Aguilera; Martin Miguel Montes; Wilson Sebastián Serra Alanís; Pablo Calviño; Héctor Samuel Vera-Alcaraz; Yamila Cardoso; Stefan Koerber; Juan Marcos Mirande (Zoologischer Anzeiger, 2025)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Differential effects of coverslip-induced hypoxia and cobalt chloride mimetic hypoxia on cellular stress, metabolism, and nuclear structure - Florencia Lamela; Ronell Bologna-Molina; Felipe Parietti; Vanesa Pereira-Prado; Magdalena Millán; Alejandro Silva; Juan Llaguno; Julia Alonso; Ariel Fernández; José Sotelo-Silveira; Manoela Domingues; Miguel Arocena; et al. (Tissue and Cell, 2024)

Analysis of thermal discomfort associated with synoptic conditions in the city of Pelotas, southernmost region of Brazil - Franciele da Costa Trassante; Rose Ane Pereira de Freitas; Anderson Spohr Nedel; Raquel Machado Machado; Marco Antônio Flores de Medeiros; Douglas da Silva Lindemann; Ana Lucia da Silva Nascimento; Fernanda Casagrande; Luis Felipe Ferreira de Mendonça; Marcelo Felix Alonso (International Journal of Biometeorology, 2024)

Growth and paralytic shellfish poisoning toxin production by a Mexican dinoflagellate strain of Alexandrium tamiyavanichii Balech (1994) under different nutrient conditions - Jorge-Gerardo Pichardo-Velarde; Norma Estrada; Rosalba Alonso-Rodríguez; Felipe Ascencio (Marine Pollution Bulletin, 2024)

Production and applications of pullulan from lignocellulosic biomass: Challenges and perspectives - Mónica María Cruz-Santos; Felipe Antônio Fernandes Antunes; Gabriel Leda Arruda; Vinicius Pereira Shibukawa; Carina Aline Prado; Nayeli Ortiz-Silos; María José Castro-Alonso; Paulo Ricardo Franco Marcelino; Júlio César Santos (Bioresource Technology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

An integrative approach method reveals the presence of a previously unreported species of Imparfinis Eigenmann and Norris 1900 (Siluriformes: Heptapteridae) in Argentina - Gastón Aguilera; Guillermo E. Terán; Juan Marcos Mirande; Felipe Alonso; Guido Miranda Chumacero; Yamila Cardoso; Sergio Bogan; Dario R. Faustino‐Fuster (Journal of Fish Biology, 2022)
Specimens of Imparfinis were recently collected in north‐western Argentina from the Bermejo River basin (Salta and Jujuy Provinces), del Valle River (Salta Province) and Horcones River (Santiago del Estero Province). An integrative approach to taxonomy, combining a detailed morphological study and molecular phylogenetic analyses, was applied to determine the species identity of these specimens. A principal components analysis of morphological data clustered the specimens from north‐western Argentina and from the Amazon basin, indicating a close morphological resemblance. Also, a molecular phylogenetic analysis showed populations of I. guttatus from Argentina and Peru forming a clade. According to the conducted haplotype network analysis these populations are distinct in two mutations. Thus, in the absence of morphological or molecular data indicating the contrary, the combined method supports the identity of the specimens from the tributaries of the Paraguay River in Argentina as I. guttatus , whose type locality is in the upper Beni River basin in Bolivia. This contribution is also the first record for this species from Argentina. The disjunct distribution of I. guttatus provides new evidence reinforcing the hypothesis for the origin of the Paraguayan ichthyofauna. We also provide an approach to the phylogenetic relationships of Imparfinis in Heptapteridae.

Novel Interactions Between Phytoplankton and Bacteria Shape Microbial Seasonal Dynamics in Coastal Ocean Waters - Nestor Arandia-Gorostidi; Anders K. Krabberød; Ramiro Logares; Ina Maria Deutschmann; Renate Scharek; Xosé Anxelu G. Morán; Felipe González; Laura Alonso-Sáez (Frontiers in Marine Science, 2022)
Trophic interactions between marine phytoplankton and heterotrophic bacteria are at the base of the biogeochemical carbon cycling in the ocean. However, the specific interactions taking place between phytoplankton and bacterial taxa remain largely unexplored, particularly out of phytoplankton blooming events. Here, we applied network analysis to a 3.5-year time-series dataset to assess the specific associations between different phytoplankton and bacterial taxa along the seasonal scale, distinguishing between free-living and particle-attached bacteria. Using a newly developed network post-analysis technique we removed bacteria-phytoplankton correlations that were primarily driven by environmental parameters, to detect potential biotic interactions. Our results indicate that phytoplankton dynamics may be a strong driver of the inter-annual variability in bacterial community composition. We found the highest abundance of specific bacteria-phytoplankton associations in the particle-attached fraction, indicating a tighter bacteria-phytoplankton association than in the free-living fraction. In the particle-associated fraction we unveiled novel potential associations such as the one between Planctomycetes taxa and the diatom Leptocylindrus spp. Consistent correlations were also found between free-living bacterial taxa and different diatoms, including novel associations such as those between SAR11 with Naviculales diatom order, and between Actinobacteria and Cylindrotheca spp. We also confirmed previously known associations between Rhodobacteraceae and Thalassiosira spp. Our results expand our view on bacteria-phytoplankton associations, suggesting that taxa-specific interactions may largely impact the seasonal dynamics of heterotrophic bacterial communities.

Silicon promotes the control of Meloidogyne incognita in lettuce by increasing ascorbic acid and phenolic compounds - Tales Arthur de Souza Alonso; Dalila Lopes da Silva; Renato de Mello Prado; Pedro Luiz Martins Soares; Luis Felipe Lata Tenesaca; Rivanildo Júnior Ferreira (Journal of Pest Science, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Molecular characterization of the spectacled caiman ( Caiman crocodilus ) in the upper Magdalena River basin, Colombia: Demographic and phylogeographic insights - Diana M. Díaz-Moreno; Felipe Hernández-Gonzalez; Juan F. Moncada-Jimenez; Cristina Mora; Carlos Prada; Gonzalo Jiménez-Alonso; Sergio A. Balaguera-Reina (Systematics and Biodiversity, 2021)

Astragallus mollissimus plant extract: a strategy to reduce ruminal methanogenesis - Pedro Antonio Ochoa-García; Robin C. Anderson; Martha María Arévalos-Sánchez; Felipe Alonso Rodríguez-Almeida; Monserrath Félix-Portillo; Alberto Muro-Reyes; Aleksandar K. Božić; Claudio Arzola-Álvarez; Agustín Corral-Luna (Tropical Animal Health and Production, 2021)

Non-fermented Dairy Desserts with Potentially Probiotic Autochthonous Lactobacilli and Products from Peel of Jabuticaba (Myrciaria cauliflora) - Marina Cínthia de Sousa; Widson Michael dos Santos; Júlia Maria Orleans da Silva; Felipe Pereira Ramos; Aline Souza de Freitas; Maria Carmélia Almeida Neta; Karina Maria Olbrich dos Santos; Flávia Carolina Alonso Buriti; Eliane Rolim Florentino (Probiotics and Antimicrobial Proteins, 2021)

Moss (Hypnum amabile) as biomonitor of genotoxic damage and as bioaccumulator of atmospheric pollutants at five different sites of Mexico City and metropolitan area - Sandra Gómez-Arroyo; Miguel Ángel Zavala-Sánchez; César Damián Alonso-Murillo; Josefina Cortés-Eslava; Omar Amador-Muñoz; Luis Felipe Jiménez-García; Ofelia Morton-Bermea (Environmental Science and Pollution Research, 2021)

Presence of Polyphenols Complex Aromatic “Lignin” in Sargassum spp. from Mexican Caribbean - Liliana Alzate-Gaviria; Jorge Domínguez-Maldonado; Rubí Chablé-Villacís; Edgar Olguin-Maciel; Rosa María Leal-Bautista; Gonzalo Canché-Escamilla; Adán Caballero-Vázquez; Cecilia Hernández-Zepeda; Felipe Alonso Barredo-Pool; Raúl Tapia-Tussell (Journal of Marine Science and Engineering, 2020)
In recent years, the massive influx of pelagic Sargassum spp. has generated great interest in the scientific community, highlighting the urgency of addressing the physiology and biochemical composition of these species. Until now, the presence of lignified cells in the tissue of Sargassum natans and Sargassum fluitans has not been reported. Although ‘‘lignin-like’’ compounds have been identified in green algae, the presence of true lignin in the Sargassum genus has not been confirmed. Our work is the first report of lignified cells forming the secondary cell wall in these Sargassum. This study used histological techniques applied to thick sections for identifying lignin-like tissues in Sargassum spp. The dyes as Safranin O and Toluidine have been used to differentiate lignin and cellulose in conducting tissue and to indicate the presence, absence, and distribution of these compounds in tissues. This work is the initial study of the cell wall heteropolymers structure and arrangement in Sargassum spp., providing insights into the unique cell wall architecture of these seaweeds.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Herbicide biomonitoring in agricultural workers in Valle del Mayo, Sonora Mexico - Ana Paola Balderrama-Carmona; Melissa Valenzuela-Rincón; Luis Alberto Zamora-Álvarez; Norma Patricia Adan-Bante; Luis Alonso Leyva-Soto; Norma Patricia Silva-Beltrán; Edgar Felipe Morán-Palacio (Environmental Science and Pollution Research, 2020)

Screening for selective anticancer activity of plants from Grazalema Natural Park, Spain - José Manuel Calderón-Montaño; Sara María Martínez-Sánchez; Estefanía Burgos-Morón; Emilio Guillén-Mancina; Julio José Jiménez-Alonso; Felipe García; Abelardo Aparicio; Miguel López-Lázaro (Natural Product Research, 2019)

Shape and size variation of Jenynsia lineata (Jenyns 1842) (Cyprinodontiformes: Anablepidae) from different coastal environments - Giselle Xavier Perazzo; Fabiano Corrêa; Pablo Calviño; Felipe Alonso; Walter Salzburger; Adriana Gava (Hydrobiologia, 2019)

Identification and genotyping of porcine circovirus type II (PCV2) in Mexico - Felipe Bedolla López; María E. Trujillo Ortega; Susana Mendoza Elvira; Victor Quintero Ramírez; Rogelio Alonso Morales; Humberto Ramírez-Mendoza; Jose I. Sanchez-Betancourt (VirusDisease, 2018)

DICER1 mutation and tumors associated with a familial tumor predisposition syndrome: practical considerations - Eduardo J. Bardón-Cancho; Ana Haro-Díaz; Francisco J. Alonso-García-de la Rosa; Jorge Huerta-Aragonés; Marina García-Morín; Felipe González-Martínez; Carmen Garrido-Colino (Familial Cancer, 2017)

Interactions between toxic (As, Cd, Hg and Pb) and nutritional essential (Ca, Co, Cr, Cu, Fe, Mn, Mo, Ni, Se, Zn) elements in the tissues of cattle from NW Spain - Marta López Alonso; Felipe Prieto Montaña; Marta Miranda; Cristina Castillo; Joaquín Hernández; José Luis Benedito (BioMetals, 2004)

Novel stop and frameshifting mutations in the autosomal dominant polycystic kidney disease 2 (PKD2) gene - Miguel Viribay; Tomohito Hayashi; Dolores Tellería; Toshio Mochizuki; David M. Reynolds; Rafael Alonso; Xose M. Lens; Felipe Moreno; Peter C. Harris; Stefan Somlo; José L. San Millán (Human Genetics, 1997)